2024
DOI: 10.3847/2041-8213/ad2073
|View full text |Cite
|
Sign up to set email alerts
|

Observation of GRB 221009A Early Afterglow in X-Ray/Gamma-Ray Energy Bands

Chao Zheng,
Yan-Qiu Zhang,
Shao-Lin Xiong
et al.

Abstract: The early afterglow of a gamma-ray burst (GRB) can provide critical information on the jet and progenitor of the GRB. The extreme brightness of GRB 221009A allows us to probe its early afterglow in unprecedented detail. In this Letter, we report comprehensive observation results of the early afterglow of GRB 221009A (from T 0+660 s to T 0+1860 s, where T 0 is the Insight-HXMT/HE trigger time) in X-ray/gamma-ray energy band (from 20 keV to 20 MeV) by Insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Given the absence of variability in the TeV light curve as observed by LHAASO, the MeV and GeV-TeV spectral components are not produced from the same emission region of the early epochs (< 500 s). In contrast, the late MeV emission (> 600 s) is temporally featurless and can be assigned to the afterglow emission component, as also considered by other authors [18,8,19,20]. We thus consider the latest (1000 − 1350 s) MeV-TeV spectrum to rise from the synchrotron and synchrotron self-Compton (SSC) radiation of the forward shock-accelerated electrons of the circum-burst medium.…”
mentioning
confidence: 88%
“…Given the absence of variability in the TeV light curve as observed by LHAASO, the MeV and GeV-TeV spectral components are not produced from the same emission region of the early epochs (< 500 s). In contrast, the late MeV emission (> 600 s) is temporally featurless and can be assigned to the afterglow emission component, as also considered by other authors [18,8,19,20]. We thus consider the latest (1000 − 1350 s) MeV-TeV spectrum to rise from the synchrotron and synchrotron self-Compton (SSC) radiation of the forward shock-accelerated electrons of the circum-burst medium.…”
mentioning
confidence: 88%
“…It consisted of a precursor of ∼10 s, a quiescent period of ∼170 s, a main emission stage of ∼60 s, and a flaring episode of ∼250 s (An et al 2023;Williams et al 2023). A jet break in the early afterglow was also observed by both GECAM-C, Insight-HXMT, and Fermi/GBM at ∼1246 s after the trigger time of Insight-HXMT (An et al 2023;Zheng et al 2024). Optical observations indicated that this burst was located at a galaxy with the redshift z = 0.151 (Castro-Tirado et al 2022).…”
Section: Introductionmentioning
confidence: 99%